Effect of Inflation, BI Rate And Net Export To USD Central Exchange Rate to Rupiahs In Bank Indonesia For 2005-2019 - Sri Harjunawati; Ida Hendarsih; Syahrial Addin; Amas Sari Marthanti (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2021)
This study discusses the USD Central Exchange Rate of USD To Rupiah at Bank Indonesia as a Dependency Factor (Y), with independent factors that can approve internal aggregates, namely In ation (X1), BI Rate (X2), and Net Exports (X3). The hypothesis used in this study is In ation (X1) that applies to the USD Middle Rate Against Rupiah at Bank Indonesia (Y), whether the BI Rate (X2) is related to the USD Middle Rate Against Rupiah at Bank Indonesia (Y), whether Net Exports (Y X3) against the USD Exchange Rate Against Rupiah at Bank Indonesia (Y), and whether In ation (X1), BI Rate (X2), and Net Exports (X3) simultaneously oppose the USD Exchange Rate Against Rupiah at Bank Indonesia (Y). The data used are secondary data released by the Indonesian Central Statistics Agency and processed using SPSS.22. The classic test is done using the Normality Test, Autocorrelation Test, and Multicollinearity Test. Hypothesis testing is done using a Simple Linear Test and Multiple Linear Test. This research resulted in a calculated value of X1 against Y of -1.318; the value of t-count X2 against Y is -1,963; and the t-value of X3 against Y is -3,803. The t-table value is negative in this study -2.16037. Multiple linear tests in this study produced a calculated F value of 4.670> 3.587 (F table). The regression equation in this study is Y = 12,226,241 - 166,022.X1 + 196,115.X2 - 0,101.X3 + e. The coe cient of R value is 0.748 and the value of R square is 0.56.